Organizational behavior today - Ross, Stanley C. (Routledge, 2021)
"This exciting new introductory text offers a new perspective on teaching organizational behavior by framing the organization as the vehicle for implementing strategic management processes, while also breaking down how the different components of an organization are designed to work together. Unlike traditional OB texts, Organizational Behavior Today emphasizes a "big picture" examination of how organizations function in a Darwinian world, in which the primary goal of an organization is survival. The book introduces readers to the three stages of the strategic management process: strategy formulation, strategy implementation, and strategic control, thereby linking the organization to its mission, vision, and strategic goals. Essential OB concepts such as work processes, policy, worker behavior, reward system, change management, and leadership development are covered, and the book also highlights the impact of technology on organizations. To support student comprehension and bring the study of OB to life, the book includes vignettes highlighting real organizations who have implemented OB processes, either successfully or unsuccessfully. End-of-chapter questions ensure that students can apply the information learned effectively. Accompanying online resources for this text, available at www.Routledge.com/9780367695095, include a test bank, PowerPoint lecture slides, and a curated list of relevant video content. The book is suitable for undergraduates and graduate students completing a first course in Organizational Behavior, as well as a practical reference for current managers wishing to optimize organizational performance"--